2013
DOI: 10.1089/scd.2012.0384
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Cell Source, Culture Methodology, Culture Location, and Individual Donors on Gene Expression Profiles of Bone Marrow-Derived and Adipose-Derived Stromal Cells

Abstract: Bone marrow (BM) stromal cells (MSCs), also known as mesenchymal stem cells, display a high degree of heterogeneity. To shed light on the causes of this heterogeneity, MSCs were collected from either human BM (n = 5) or adipose tissue (AT) (n = 5), and expanded using 2 different culture methods: one based on fetal calf serum, and one based on human platelet lysate. After initial expansion, MSCs were frozen, and the vials were transported to 3 different laboratories and grown for 1 passage using the same brand … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 71 publications
1
32
0
Order By: Relevance
“…15 Even the other association factors, ages, gender, cell isolated strategy, and storage method could possibly affect the biological properties of ADSC. 16 In this study, we verified the culture strategy could amplify ADSC effectively and effectively express stemness genes, SOX2, OCT4, NANOG, and KLF4 continuously.…”
Section: Discussionmentioning
confidence: 60%
“…15 Even the other association factors, ages, gender, cell isolated strategy, and storage method could possibly affect the biological properties of ADSC. 16 In this study, we verified the culture strategy could amplify ADSC effectively and effectively express stemness genes, SOX2, OCT4, NANOG, and KLF4 continuously.…”
Section: Discussionmentioning
confidence: 60%
“…In the future it may be necessary to develop a classification system to identify predictors of differentiation potential. Although some work has been done profiling hASC using cell surface markers, 6,27 microarray surveys of gene expression, 28,29 and microRNA profiles, 12 these data have not been extensively correlated with hASC potency. It is important to note that the ages and number of donor cell lines incorporated in this study were based on the availability of donor cell lines within our laboratory bank of cells.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies revealed several similarities and differences between BMSCs and ASCs. For example, ASCs are able preserve cardiac function following myocardial infarction but the BMSCs are not [7]; both BMSCs and ASCs adhered to and proliferated similarly on nanoparticle-coated plates [8]; both stem cells presented a highly similar morphology and marker expression in an undifferentiated state [9, 10], but compared to ASCs, BMSCs showed an enhanced capacity to differentiate into the chondrogenic lineage [9]; ASCs displayed more resistance to chemotherapy than BMSCs and might therefore be more advantageous for application in clinical settings [11]; cell origin and abundance were determined as vital factors in stem cell selection, and it was found that adipose tissue is a more promising source of stem cells [4, 13, 14]; and finally, cyclic hydrostatic pressure could induce human ASCs to undergo chondrogenic differentiation in a manner similar to BMSCs [15]. Taken together, past and present studies indicate that, despite some differences between BMSCs and ASCs in their expression of surface proteins markers, it seems that their myogenic potential is similar (albeit not identical); and it also suggests that ASCs may be a good candidate for use in skeletal muscle tissue engineering research because they could be isolated in abundant quantities from a tissue which can be obtained by a procedure that is minimally invasive, in comparison to that required for BMSCs.…”
Section: Discussionmentioning
confidence: 99%
“…They have been examined in a myocardial infarction model [7], expanded on a nanoparticle-coated substratum [8], and subjected to chondrogenic differentiation [9]. Additionally, the expression of cell surface markers [10], sensitivity to chemotherapeutic agents [11], morphological, molecular and functional differences [12], biological characteristics and multilineage differentiation [13], the impact of cell source, culture methodology, culture location, and individual donors on gene expression profiles [14], and the effects of cyclic hydrostatic pressure on chondrogenesis and cell viability [15] have also been studied. MSCs with myogenic potential that can fuse with co-cultured myoblasts to produce myotubes in vitro can be obtained from 2 sources, bone marrow and adipose tissues.…”
Section: Introductionmentioning
confidence: 99%